IMPROVING THE PROCESS OF PRACTICAL PHYSICAL TRAINING OF PHYSICAL CULTURE AND SPORTS SPECIALISTS - Eshimov, Temur Alijonovich (Educational Research in Universal Sciences, 2023)
The article presents the results of scientific research conducted on the importance of systematic performance of volleyball sports exercises by students during the years of study in increasing the level of professional-practical physical fitness of students of Islamic culture.